2022
DOI: 10.1038/s41396-022-01220-z
|View full text |Cite
|
Sign up to set email alerts
|

Meta-omics-aided isolation of an elusive anaerobic arsenic-methylating soil bacterium

Abstract: Soil microbiomes harbour unparalleled functional and phylogenetic diversity. However, extracting isolates with a targeted function from complex microbiomes is not straightforward, particularly if the associated phenotype does not lend itself to high-throughput screening. Here, we tackle the methylation of arsenic (As) in anoxic soils. As methylation was proposed to be catalysed by sulfate-reducing bacteria. However, to date, there are no available anaerobic isolates capable of As methylation, whether sulfate-r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 87 publications
0
35
0
Order By: Relevance
“…For example, in the cultures amended with As, Deltaproteobacteria populations did not transcribe arsM, although they contributed most of the arsM sequences. 70 Our study identified, for the first time, the considerable abundance and active expression of arsC in phylum Aquificae.…”
Section: Microbial Metabolisms and As Cycling Strategiesmentioning
confidence: 99%
“…For example, in the cultures amended with As, Deltaproteobacteria populations did not transcribe arsM, although they contributed most of the arsM sequences. 70 Our study identified, for the first time, the considerable abundance and active expression of arsC in phylum Aquificae.…”
Section: Microbial Metabolisms and As Cycling Strategiesmentioning
confidence: 99%
“…Some anaerobic microorganisms are thought to produce a toxic trivalent MMA(III) to kill their competitors, 78 which was hypothesized to promote arsenic methylation in a microbial community. 50 Indeed, cells expressed with arsM usually conveyed some level of resistance to MMA(III) 79 and so did arsenic-methylating microorganisms. 31 Besides, M. thermophila contains the arsR gene (Figure S16a), which is autoregulated and is typically part of an operon that contains other ars genes involved in arsenic detoxification.…”
Section: ■ Discussionmentioning
confidence: 99%
“…BXM 49 and Paraclostridium sp. strain EML, 50 and ArsM enzymes purified from Desulfosporosinus meridiei and Desulfotonmaculum gibsoniae 14 were able to efficiently methylate arsenite. Two pure methanogens have been investigated for arsenic methylation as well, i.e., Methanosarcina mazei (M. mazei) Go1 40,51 and Methanosarcina acetivorans (M. acetivorans) C2A.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Similarly, the application of combined metagenomics, metatranscriptomics, and metaproteomics enabled the identification of the microorganisms actively methylating arsenic in anoxic soil-derived microbial cultures (Viacava et al, 2022). Furthermore, based on the analysis of the metagenome-assembled genomes of microorganisms expressing arsenite S-adenosylmethionine methyltransferase (ArsM), a targeted cultivation strategy was developed, resulting in the isolation of the Paraclostridium sp.…”
Section: Overview Of -Omics Integration In Soil Sciencementioning
confidence: 99%